The influence of North African and Middle Eastern architectures in the birth and development of modern architecture in Central Europe (1898–1937). Issue 2 (3rd July 2018) - Jiménez-Vicario, Pedro Miguel; García-Martínez, Pedro; Ródenas-López, Manuel Alejandro
Abstract : This paper analyses the relationship and influence of North African and Middle Eastern architectures on the birth and development of modern architecture in Central European countries during the first three decades of twentieth century. The authors examine the contacts that the Central European architectural avant-garde had with the architecture of North Africa and the Middle East, and analyse how certain German and Austrian architects reacted to what they witnessed and how they interpreted it in their ensuing designs and projects. Architects in both countries were seeking a new formal code that responded to the needs of the era. The authors' aim here is to determine how and to what extent each country's avant-garde adopted the repertoire of vernacular Mediterranean architecture during the critical period of development of the Modern Movement.